IMPLEMENTASI KURIKULUM MERDEKA DI SEKOLAH KHUSUS KAK SETO KOTA TANGERANG SELATAN - Mahmud, Fuad Khalis; Mirnawati, Mirnawati; Kusumastuti, Dewi Ekasari (Al-Falah: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2023)
Abstract The "Kurikulum Merdeka," as a new educational policy, requires extensive references to support its implementation. This research aims to provide an overview and description of the implementation of the "Kurikulum Merdeka" at Kak Seto Special School, with the purpose of serving as a reference for other special schools or exceptional education institutions in implementing the "Kurikulum Merdeka." Primary data for this study were collected from the school principal, curriculum coordinator, and 4th and 6th grade homeroom teachers. Meanwhile, secondary data encompassed school documents and curriculum implementation guidelines. Data collection methods included observation, interviews, and documentation. Data validity was ensured through the triangulation technique of sources and methods. The data analysis process involved data collection, data reduction, data presentation, and drawing conclusions. The research findings revealed that the implementation of the "Kurikulum Merdeka" at Kak Seto Special School consists of six main components. Firstly, the teaching and assessment process begins with the formulation of the Learning Objective Flow (Alur Tujuan Pembelajaran or ATP), Learning Achievement (Capaian Pembelajaran or CP), Learning Objective (Tujuan Pembelajaran or TP), teaching modules, and Individual Education Program (Program Pendidikan Individual or PPI). This is followed by the implementation of teaching and assessment based on the instructional materials previously designed. Secondly, the process of developing the Operational Curriculum of the Educational Unit. Thirdly, the formulation and execution of projects to reinforce the Pancasila student profile, a unique co-curricular activity of the "Kurikulum Merdeka." Fourthly, the collaboration activities with students' parents through parent meetings and inspiring classes. Fifthly, identifying challenges in implementing the "Kurikulum Merdeka" that involve adjustments to the components of the curriculum. Sixthly, efforts to address these challenges through training and discussions. Keyword: Implementation, Independent Curriculum, Kak Seto Special School.  Abstrak Kurikulum Merdeka, sebagai kebijakan pendidikan yang baru, memerlukan referensi yang luas untuk mendukung penerapannya. Penelitian ini bertujuan untuk memberikan gambaran dan deskripsi mengenai pelaksanaan Kurikulum Merdeka di Sekolah Khusus Kak Seto, dengan tujuan agar informasi ini dapat dijadikan sebagai referensi bagi sekolah-sekolah khusus atau sekolah luar biasa dalam mengimplementasikan Kurikulum Merdeka. Data primer dalam penelitian ini dikumpulkan dari kepala sekolah, koordinator kurikulum, serta guru wali kelas 4 dan 6. Sementara itu, data sekunder meliputi dokumen sekolah dan panduan-panduan implementasi kurikulum. Metode pengumpulan data mencakup observasi, wawancara, dan dokumentasi. Validitas data dijamin melalui teknik triangulasi sumber dan metode. Proses analisis data meliputi pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian mengungkapkan bahwa implementasi Kurikulum Merdeka di Sekolah Khusus Kak Seto terdiri dari enam komponen utama. Pertama, proses pembelajaran dan asesmen dimulai dengan penyusunan Alur Tujuan Pembelajaran (ATP), Capaian Pembelajaran (CP), Tujuan Pembelajaran (TP), modul pengajaran, dan Program Pendidikan Individual (PPI). Langkah ini diikuti oleh pelaksanaan pembelajaran dan asesmen berdasarkan perangkat pengajaran yang telah dirancang sebelumnya. Kedua, proses penyusunan Kurikulum Operasional Satuan Pendidikan. Ketiga, penyusunan serta pelaksanaan projek penguatan profil pelajar Pancasila sebagai kegiatan kokurikuler yang menjadi ciri khas Kurikulum Merdeka. Keempat, pelaksanaan kegiatan kolaborasi dengan orang tua siswa melalui pertemuan orang tua dan kelas inspiratif. Kelima, mengidentifikasi kendala dalam implementasi Kurikulum Merdeka yang melibatkan penyesuaian dengan komponen-komponen Kurikulum Merdeka. Keenam, upaya dalam mengatasi kendala-kendala tersebut melalui pelatihan dan diskusi. Kata kunci: Implementasi, Kurikulum Merdeka, Sekolah Khusus Kak Seto.